DETERMINAN AUDIT DELAY (Media Riset Akuntansi, 2022)
This study aims to discuss the influence size of company, size of the public accounting firm, implementation of international financial reporting standards, and auditor changes to audit delay. The population of this study is mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2015- 2018 amounting to 200. The sample selection method used is purposive sampling method. Based on these methods a sample size of 88 was obtained. Data analysis method uses multiple linear regression analysis with SPSS software version 25. Data analysis method uses multiple linear regression analysis (multiple regression analysis) with SPSS software version 25. The results of this study indicate that the size of the Public Accounting Firm has a negative effect on Audit Delay, while the Company Size, Application of International Financial Reporting Standards, and Auditor Substitution has no effect Audit Delay.